Redox and Ligand Exchange during the Reaction of Tetrachloroaurate with Hexacyanoferrate(II) at a Liquid-Liquid Interface: Voltammetry and X-ray Absorption Fine-Structure Studies. (1st February 2016) - Uehara, Akihiro; Chang, Sin-Yuen; Booth, Samuel G.; Schroeder, Sven L.M.; Mosselmans, J.Frederick W.; Dryfe, Robert A.W.
Abstract: Voltammetry for charge (ion and electron) transfer at two immiscible electrolyte solutions (VCTIES) has been used to provide insight into the ligand exchange and redox processes taking place during the interfacial reaction of aqueous hexacyanoferrate(II) with tetrachloroaurate ([AuCl4 ] − ) in 1, 2-dichloroethane (DCE). VCTIES permitted the detection of the reactants, intermediates and products at the liquid/liquid interface. A model for the sequence of interfacial processes was established with the support of speciation analysis of the key elementary reactions by X-ray absorption spectroscopy (XAS). The potential-driven transfer of [AuCl4 ] − from the organic into the aqueous phase is followed by reduction and ligand exchange by the aqueous hexacyanoferrate(II) to form dicyanoaurate ([Au(CN)2 ] − ). Inferences from the reactions point to the likely formation of [AuCl2 ] − during the reduction sequence. The reaction is influenced by ligand exchange equilibria between [AuCl4 ] −, [AuCl3 (OH)] – and [AuCl2 (OH)2 ] – which are shown to be dependent on the chloride ion concentration and pH of the solution. The difference between the Gibbs energy of transfer at the water | DCE interface ( Δ G D C E W ° ) of AuCl4 – and [AuCl3 (OH)] –, and the difference between [AuCl3 (OH)] – and [AuCl2 (OH)2 ] – were found to change by a value close to the difference between Δ G D C E W ° of Cl – and that of OH – . The intermediate Au(I) species, [AuCl2 ] −, was seen to decompose at neutral pH and in the absence of Cl – in water to form metallic Au, although it was stable in >10 mM HCl for an hour. Time-dependent VCTIES and X-ray absorption fine structure (XAFS) speciation analysis of the homogeneous aqueous phase indicate that reaction between [AuCl4 ] − and hexacyanoferrate(II) is accompanied by the formation of an intermediate ionic species, formed when the concentration of [AuCl4 ] − is close to that of hexacyanoferrate(II). This species, whose identity was not precisely determined, was also generated by reaction between [AuCl2 ] − and hexacyanoferrate(III). The species is shown by VCTIES to be more hydrophilic than [Au(CN)2 ] −, [AuCl2 ] − and [AuCl4 ] − .